Access and care issues in urban urgent care clinic patients - Scott, David R (BioMed Central, 2009)
BACKGROUND: Although primary care should be the cornerstone of medical practice, inappropriate use of urgent care for non-urgent patients is a growing problem that has significant economic and healthcare consequences. The characteristics of patients who choose the urgent care setting, as well as the reasoning behind their decisions, is not well established. The purpose of this study was to determine the motivation behind, and characteristics of, adult patients who choose to access health care in our urgent care clinic. The relevance of understanding the motivation driving this patient population is especially pertinent given recent trends towards universal healthcare and the unclear impact it may have on the demands of urgent care. METHODS: We conducted a cross-sectional survey of patients seeking care at an urgent care clinic (UCC) within a large acute care safety-net urban hospital over a six-week period. Survey data included demographics, social and economic information, reasons that patients chose a UCC, previous primary care exposure, reasons for delaying care, and preventive care needs. RESULTS: A total of 1, 006 patients were randomly surveyed. Twenty-five percent of patients identified Spanish as their preferred language. Fifty-four percent of patients reported choosing the UCC due to not having to make an appointment, 51.2% because it was convenient, 43.9% because of same day test results, 42.7% because of ability to get same-day medications and 15.1% because co-payment was not mandatory. Lack of a regular physician was reported by 67.9% of patients and 57.2% lacked a regular source of care. Patients reported delaying access to care for a variety of reasons. CONCLUSION: Despite a common belief that patients seek care in the urgent care setting primarily for economic reasons, this study suggests that patients choose the urgent care setting based largely on convenience and more timely care. This information is especially applicable to the potential increase in urgent care volume in a universal healthcare system. Additionally, this study adds to the body of literature supporting the important role of timely primary care in healthcare maintenance.